Documenting systemic school reform from vision to standards and assessment: The case of DLSU - Plata, Sterling M. (Animo Repository, 2013)
Many schools find systemic reform difficult to implement as there are many factors and stakeholders who may hinder this initiative. This case study looks into systemic reform process in a higher education institution through policy document analysis and participant observation. It also reports the process of aligning the vision, standards, and assessment in a department. The results showed that systemic school reform can be realized with a leadership that can align the curriculum, pedagogical framework, and professional development. The consensus-building processes in the department level were also seen as a mechanism to ensure that every member of the faculty would share a common vision for the students. © 2013, Plata; licensee Springer.